DEVELOPMENT OF AUGMENTED REALITY-ASSISTED ZIG-ZAG BOOK MEDIA IN NARRATIVE WRITING LEARNING IN ELEMENTARY SCHOOL - Moh. Farizqo Irvan; Sutaryono; Galih Mahardika Christian Putra; Nurdin Munthe; Norita Agustina Subagyo (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses 1) development of a zig-zag book assisted by augmented reality to improve students' narrative essay writing skills that meet the eligibility criteria according to the experts and 2) to determine the effectiveness of a zig-zag book assisted by augmented reality in improving writing narrative essay skills for fourth-grade elementary students. The research method used is Research and Development with the ADDIE model. The research subjects were fourth-grade elementary students in Semarang. Data collection techniques used interviews, questionnaires, scales, tests, and performance. Data were analyzed by descriptive analysis, dependent sample t-test with prerequisite test for normality and homogeneity tests, and n-gain. The research results reveal that the media were considered very feasible to use by media and material experts. In addition, the developed media was also effective in improving the writing narrative essay skills based on the n-gain value of 0.65 with the moderate improvement category. Thus, the Zig-Zag book media assisted by Augmented Reality can be recommended to be applied in improving narrative essay writing skills of fourth-grade elementary students.